Smart Educational System: Web-Based Low Cost Remote Laboratory for Electronic Practical Work - Abouhilal, A.; Moulay taj, A.; Taifi, N.; Malaoui, A. (International Journal of Engineering and Technology, 2019)
The implementation of smart technologies is an important part of scientific research especially in the areas of new information and communication technologies, the Internet of Things, wireless sensor network. Among other things, smart educational systems have been a success through videoconferences, classroom response systems and remote labs. Scientific research on remote laboratories has undergone remarkable development in recent years. The remote practical work often uses very expensive proprietary instruments and software. The purpose of this paper is to present a low-cost architecture based on the co-operation of two embedded systems, Raspberry and Arduino. The student accesses the practical work via a web page developed with HTML / Javascript provided by a NodeJs server hosted in the Raspberry. A software oscilloscope has been developed with Processing integrable in the web page to visualise the measured signals from the practical work board.Â Â